Democratic Representation in Plurinational States The Kurds in Turkey (Comparative Territorial Politics, 2018)
This book examines modalities for the recognition and political participation of minorities in plurinational states in theory and in practice, with a specific reference to the Republic of Turkey and the resolution of the Kurdish question. Drawing on the experience of Spain and Eastern Europe and other recent novel models for minority accommodation, including the Ottoman experience of minority autonomy (the Millet System), the volume brings together researchers from Turkey and Europe more broadly to develop an ongoing dialogue that analytically examines various models for national minority accommodation. These models promise to protect the state's integrity and provide governmental mechanisms that satisfy demands for collective representation of national communities in the framework of a plurinational state. Ephraim Nimni is Visiting Fellow in the Centre for the Study of Ethnic Conflict at Queen's University Belfast, UK. He has published widely on minority rights, models of national self-determination that do not require separate nation states, multiculturalism and the applicability of the national cultural autonomy model to contemporary multination states, and on the Israeli Palestinian conflict. Elçin Aktoprak was Assistant Professor at the Faculty of Political Sciences, Ankara University, Turkey, until she was dismissed as per the emergency decree in February 2017. Her research interests are theories of nationalism, minority issues in Europe, the Kurdish question, conflict resolution and peace studies. .